Vergi usul kanununda hürriyeti bağlayıcı cezalar - Yiğit, Uğur (My University, 2003)
HÜRRİYETİ BAĞLAYICI CEZA İLE CEZALANDIRILACAK VERGİ SUÇ VE CEZALARI 213 sayılı Vergi Usul Kanununda düzenlenen Hürriyeti Bağlayıcı Ceza İle Cezalandırılacak Vergi Suç ve Cezaları; Ceza Hukuku ilkeleri (Türk Ceza Hukuk Sistemi) ve VUK'nun kendi içerisinde yer alan hükümler çerçevesinde incelenmiştir. İncelemede Ceza ve Ceza Usul Hukuku ilke, kural ve yöntemleri olmak üzere Yargı kararları ve Doktrine ait görüşlerinden yararlanılmıştır. Tez planı, VUK düzenlemesine parelel olarak üç bölümden oluşmaktadır. Birinci Bölümde; Genel Hükümler başlığı altında Birinci Kısımda; vergi hukuku ve ceza hukuku ilişkisi, İkinci Kısımda; Ceza Hukuku anlamında Suç ve Ceza, Üçüncü Kısımda; Vergi Suç ve Cezaları incelenmiştir. İkinci Bölümde; Özel Hükümler, Hürriyeti Bağlayıcı Vergi Suç ve Cezaları başlığı altında sırasıyla, Vergi Kaçakçılığı, Vergi Gizliliğine Uymama, Vergi Gizliliğine Yasayla Getirilen İstisnaların Kötüye Kullanılması suçları ve Mükellefin Özel İşlerini yapma suçu, Suçun; konusu, faili, unsurları, cezası, ile Suçun cezalandırılmasında uygulanacak Usul hükümleri yönünden incelenmiştir. Üçüncü Bölümde; Vergi Suç ve Cezalarının Kalkması başlığı altında Vergi Suçluluğunu kaldıran nedenler kısmında Pişmanlık ve Islah, Mücbir Sebep, Vergi Cezalarını sona erdiren nedenler kısmında Ölüm, Zamanaşımı, Af ve Tarhiyat Öncesi Uzlaşma konuları incelenmiştir. Sonuç bölümünde ise Hürriyeti Bağlayıcı Suç ve Cezalara ilişkin genel bir değerlendirme ve öneriler yer almıştır. Name and Surname: Uğur YIĞIT Main Discipline: Finance Course: Fiscal Law Consultant Instructor: Dr. Veysi SEVIĞ Type of Thesis and Date: Doctorate - May 2003 Key Words: Freedom Restricting Tax Penalties Tax Offenses and Penalties Tax Smuggling

TAX OFFENSES AND PENALTIES PUNISHED WITH FREEDOM RESTRICTING PENALTIES The Tax Offenses and Penalties Punished with Freedom Restricting Penalties which are regulated under Tax Regime Law no 213 have been studied in the frame of principles of Penal Law (Turkish Penal Law System) and general provisions of Tax Regime Law. This study referred in some ways to resolutions and doctrinal opinions giving priority to principles, rules and methods of Penal and Penal Regime Law. The thesis consists of three chapters in parallel with regulations of Tax Regime Law. At the first chapter, the relations of tax law and penal law have been studied in the first section under heading of General Provisions. The second section in this chapter studied Crime and Punishment in means of Penal Law, the third section studies Tax Offenses and Penalties. At the second chapter, under the heading of Special Provisions; the subjects Tax Offenses and Penalties Punished with Freedom Restricting Penalties, Tax Evasion, Failing to Comply with Tax Privacy, The Offense of Abusing the Exclusions to Tax Privacy that are Regulated by Law, The Offense of Implementing Private Businesses of the Tax Payer have been studied through the aspects of the subject, perpetrator, penalty and the methods of penalization of the offense. At the third chapter titled Abrogating of Tax Offenses and Penalties, the first heading The Reasons Abrogating the Tax Guiltiness studied Repentance and Rehabilitation and Force Major. The second heading The Reasons Ending Tax Penalties studied Death, Prescription and Compromise before Tax Forgiveness and Assessment. The study concluded with general assessment of Freedom Restricting Offenses and Penalties and Recommendations.
Keywords: Hukuk; Vergi Hukuku